Caring for - caring about: negotiations of values in pastoral care - Christoffersen, Mikkel Gabriel; Haußmann, Annette; Austad, Anne (Religions, 2024)
The term “care” in pastoral care means caring for others. Yet those who care for others in pastoral conversations can also be defined existentially as people who care about the world, that is, people who hold values. This article explores how caring for and caring about commence in pastoral practice, with special attention paid to conflicts of values in pastoral conversations. The article proposes a typology of subjects for value conflicts in pastoral care, and it proposes a set of strategies for navigating those conflicts. We base both proposals on an analysis of German and Norwegian verbatims, i.e., protocols of pastoral caregivers’ memories of pastoral care encounters. These verbatims highlight that while pastoral caregivers and care seekers have different roles and obligations in pastoral care, an existential encounter occurs which has its own potentials and pitfalls. Thereby, we draw attention to the necessary negotiations of values that transpire in pastoral conversations in postsecular societies.